PENGARUH SOFTSKILLS (INTRAPERSONAL SKILLS) TERHADAP KINERJA TENAGA PEMASAR PROPERTI - Kristina, Helena J; Laurence, Laurence; Mahatmaja, Wisang (Industrial and Systems Engineering Assessment Journal (INASEA), 2011)
These days, it has become a necessity for the property industry businesses for developing. These property businesses are usually marketed by a property broker. These growths in the property industry had made people starting to realize property as an opportunity for business, therefore the number of property businesses increasing. In order to compete, property marketing human resources need to have soft skills. This research is conducted using three independent variables, consists of self-leadership, self-efficacy and achievement motivation. The data obtained by distributing questionnaires to marketers in BSD property. Research questionnaire distributed to 100 respondents. The data were processed using validity test, reliability test, Principal Component Analysis method and multiple analysis regression. Results of the study shows that the Selfleadership has a positive influence on the level of sales per year that is equal to 3 times against property units sold. Self-efficacy has a positive influence on the level of sales per year, which is 2 times of property units sold. Motivation is not proven to have significant influence on the level of sales.